Ibn Hazm: Profile of a Muslim Scholar (American Journal of Islam and Society, 2013)
As one of history’s most prolific Muslim writers, the theologian and jurist IbnHazm (d. 1064) had a remarkably successful intellectual career. Scholars continueto argue over him, perhaps due to his own diverse perspectives, potentials,and achievements. I consider his multiple achievements, notwithstandingany deserved negative impressions, a cause for celebrating this intellectualgiant. Consequently, it is appropriate that he be profiled here. While this formatmay be restrictive, I hope to pursue some specific aspects in subsequent editorialsto paint a more comprehensive and coherent picture of this multifacetedscholar. Charles Pellat, in his article on “Ibn îazm al-Andalus¥” writes:“Ab´ Muúammad ‘Al¥ ibn Aúmad ibn Sa‘¥d ibn îazm, a poet, man-of-letters,historian, polemist, juriconsult, theologian, logician, metaphysician, and psychologist,was certainly one of the most refined and productive representativesof the Arab culture in Spain.” ..